Importance of the Number of Retreived Lymph Nodes During Cystectomy - Karadeniz, Tahir; Baran, Caner; Topsakal, Medih; Kavukcu, Ender (Urology Journal, 2011)
Purpose: To evaluate the effect of the number of dissected lymph nodes (LNs) during radical cystectomy on survival outcomes. Materials and Methods: Medical files of 211 patients who underwent cystectomy between 1996 and 2009 were retrospectively evaluated. Seventy-four patients were included in the study and divided into two groups regarding the median number of retrieved LNs (median number = 13); 36 patients in the 1st and 38 in the 2nd group. Radical cystectomy, urinary diversion, and pelvic LN dissection were done in all the patients. When necessary, adjuvant chemotherapy was applied. Kaplan-Meier survival analysis was performed to compare survival outcomes of the groups. Results: Of 74 patients, 67 (90.5%) were men and 7 (9.5%) were women, with the mean age of 61.7 years (range, 39 to 83 years). Age distribution, pathologic stages, carcinoma in situ occurrence, adjuvant chemotherapy rates, LN involvement, and median follow-up period were similar in both groups. Mean dissected LNs number in the 1st and 2nd groups was 6.17 (range, 1 to 12) and 21.6 (range, 13 to 41), respectively. Five-year estimated overall survival rates were 24.5% and 60.5% (P = .002) while five-year estimated disease-specific survival rates were 43.7% and 74.4% (P = .049), respectively. Conclusion: Although exact guidelines are not described, it seems that dissection of high number of LNs during radical cystectomy is crucial.